International Visibility of Balkan Economists in the Post-Socialist Era - ÇOKGEZEN, JALE; ÇOKGEZEN, MURAT (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2015)
During the socialist era, economists in the Balkan countries rarely published their work in the West due to political restrictions, methodological differences with the West, and inadequacy in Western languages. After the collapse of socialism, political barriers were lifted, a Western style of education in economics was adopted, and English began to be taught widely as the common language in the academic realm. The aim of this study is to discuss the impact of these policies on the publication performance of economists in the former socialist countries of the Balkans region. The results reveal that the number of international publications increased gradually over the post-socialist period and fast-reforming countries performed better than the slow movers.
Keywords: economics education; Balkans; publications; freedom